Packet data communications over coded CDMA. Part I achievable spectral efficiency of CDMA systems with turbo codes and linear multiuser receivers. - Seokhyun Yoon (IEEE Transactions on wireless communications)
In this two part paper, we consider a packet data communication over code-division multiple-access (CDMA) system. As a preliminary, this part of the paper highlights the practically achievable spectral efficiency of a CDMA system with turbo codes and multiuser detection, assuming the use of hybrid type-I automatic-repeat-request. We also investigate the effect of code rates on the performance of systems with matched filter and linear minimum mean square error (MMSE) receivers, respectively. For a given ensemble distance spectra of punctured turbo codes, we use an improved union bound to evaluate the error probability of maximum likelihood turbo decoder with matched filter receiver and with linear MMSE receiver front-end, and then compute the corresponding throughput and spectral efficiency as a function of system load. The results show that with 1/3 rate turbo code and matched filter receiver a spectral efficiency of around 1.1 b/s/Hz can be obtained, while, by employing a linear MMSE receiver, the spectral efficiency can be improved further up to 1.6 b/s/Hz. The results also show that the spectral efficiency with a linear MMSE receiver saturates at a code rate of about 4/5, i.e., does not improve further with lower rate coding, while, for matched filter receivers, better performance can be obtained with lower code rate. Theoretically, as the system load goes to infinity, the spectral efficiency of linear MMSE receiver converges to that of matched filter receiver. In a practical situation, however, there exists a noticeable performance gap between the two receivers unless a very low rate code is used.